Pengaruh Sistem Pelacakan Online Dan Ketepatan Waktu Pengiriman Terhadap Kepuasan Pelanggan (Studi Kasus JNE Cabang Utama Malang) - Muchammad Maslikhan; Muhammad Ridwan Basalamah; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to analyze the effect of online tracking systems and on time delivery on customer satisfaction at JNE Malang. This research uses quantitative research. The location of this research was conducted at JNE Main Branch Malang, Jl. Hamid Rusdi No. 95, Bunulrejo, Kec. Blimbing, Malang City, East Java 65121. The population used in this study were all users of JNE Main Branch Malang and the number of samples taken in this study was 100 respondents. The results of this study state that the Effect of Online Tracking System and Timeliness on Customer Satisfaction is significant, the Effect of Online Tracking System on Customer Satisfaction is significant and the Effect of Timeliness on Customer Satisfaction is significant.